Anti-Corrosion Mechanism of Parsley Extract and Synergistic Iodide as Novel Corrosion Inhibitors for Carbon Steel-Q235 in Acidic Medium by Electrochemical, XPS and DFT Methods - Wan, Shan; Chen, Huikai; Zhang, Tian; Liao, Bokai; Guo, Xingpeng (Frontiers in Bioengineering and Biotechnology, 2021)
The parsley extract (PLE) was obtained using absolute ethyl alcohol. The PLE and synergistic iodide were firstly utilized as efficacious corrosion inhibitors to slow down the corrosion rate of Q235 carbon steel in 0.5 mol/L H2SO4 solution. The anti-corrosion performance was researched by weight loss method, electrochemical tests, surface analysis and quantum chemistry calculation. Results of electrochemical and weight loss tests show that the synergetic PLE and I- exhibit the optimal corrosion inhibition efficiency 99%. The combined inhibitor displays the favourable long-term corrosion inhibition effect, and the inhibition efficiency can maintain more than 90% after 144 h immersion. The introduction of I- makes carbon steel surface with higher negative charge amount, which could be beneficial to the interaction between corrosion inhibitor and Fe atoms. The adsorption behaviour obeys the Langmuir isotherm adsorption, and involves chemical and physical adsorption. On the basis of electrochemical consequences and theoretical calculation, the adsorption process and anti-corrosion mechanisms are further explored.